Glycerol-3-Phosphate Shuttle Is Involved in Development and Virulence in the Rice Blast Fungus Pyricularia oryzae - Shi, Yongkai; Wang, Huan; Yan, Yuxin; Cao, Huijuan; Liu, Xiaohong; Lin, Fucheng; Lu, Jianping (Frontiers in Plant Science, 2018)
The glycerol-3-phosphate (G-3-P) shuttle is an important pathway for delivery of cytosolic reducing equivalents into mitochondrial oxidative phosphorylation, and plays essential physiological roles in yeast, plants, and animals. However, its role has been unclear in filamentous and pathogenic fungi. Here, we characterize the function of the G-3-P shuttle in Pyricularia oryzae by genetic and molecular analyses. In P. oryzae, PoGpd1 is involved in conidiation and utilization of several carbon sources (pyruvate, sodium acetate, glutamate, and glutamine). PoGpd2 is essential for glycerol utilization and fungal development. Deletion of PoGPD2 led to delayed aerial hyphal formation, accelerated aerial hyphal collapse, and reduced conidiation on complete medium (CM) under a light-dark cycle. Aerial mycelial surface hydrophobicity to water and Tween 20 was decreased in ΔPogpd2. Melanin synthesis genes required for cell wall construction and two transcription factor genes (COS1 and CONx2) required for conidiation and/or aerial hyphal differentiation were down-regulated in the aerial mycelia of ΔPogpd2 and ΔPogpd1. Culturing under continuous dark could complement the defects of aerial hyphal differentiation of ΔPogpd2 observed in a light-dark cycle. Two light-sensitive protein genes (PoSIR2 encoding an NAD+-dependent deacetylase and TRX2 encoding a thioredoxin 2) were up-regulated in ΔPogpd2 cultured on CM medium in a light-dark cycle. ΔPogpd2 showed an increased intracellular NAD+/NADH ratio and total NAD content, and alteration of intracellular ATP production. Culturing on minimal medium also could restore aerial hyphal differentiation of ΔPogpd2, which is deficient on CM medium in a light-dark cycle. Two glutamate synthesis genes, GDH1 and PoGLT1, which synthesize glutamate coupled with oxidation of NADH to NAD+, were significantly up-regulated in ΔPogpd2 in a light-dark cycle. Moreover, deletion of PoGpd1 or PoGpd2 led to reduced virulence of conidia or hyphae on rice. The glycerol-3-phosphate shuttle is involved in cellular redox, fungal development, and virulence in P. oryzae.